2010
DOI: 10.1039/c0cc01535k
|View full text |Cite
|
Sign up to set email alerts
|

Designing late-transition metal catalysts for olefin insertion polymerization and copolymerization

Abstract: The innovation of polyolefin with unique architecture, composition and topology continues to inspire polymer chemists. An exciting recent direction in the polyolefin field is the design of new catalysts based on late-transition metals. In this review, we highlight recent developments in rationally designing late-transition metal catalysts for olefin polymerization. The examples described in this review showcase the power of the design of well-defined late-metal catalysts for tailored polyolefin synthesis, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
123
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(125 citation statements)
references
References 158 publications
1
123
0
1
Order By: Relevance
“…Meanwhile, the chain transfer process proceeds through the 5-coordinate transition state which undergoes the chain transfer with the incoming ethylene monomer from the axial sites of the nickel center [9]. The steric crowding at the axial sites is critical for suppressing the associative chain transfer process with the ethylene monomer at the axial site and results in the formation of a high molecular-weight polymer [12] [13] [14].…”
Section: Effects Of Ortho-substituent On Catalyst Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the chain transfer process proceeds through the 5-coordinate transition state which undergoes the chain transfer with the incoming ethylene monomer from the axial sites of the nickel center [9]. The steric crowding at the axial sites is critical for suppressing the associative chain transfer process with the ethylene monomer at the axial site and results in the formation of a high molecular-weight polymer [12] [13] [14].…”
Section: Effects Of Ortho-substituent On Catalyst Propertiesmentioning
confidence: 99%
“…A major research direction in this field is modification of the α-diimine ligand or bis(imino)pyridine ligand structures [9] [10] [11]. For example, orthosubstituents of the aryl rings on the imino groups play an important role in controlling the molecular weight of the products.…”
Section: Introductionmentioning
confidence: 99%
“…50 In contrast, Pd and Ni complexes with diimine ligands are effective for a-olefin polymerization. 51 Conventional catalysts such as zirconocenes produce linear polyethylene and polyolefins with alkyl side chains in the polymerization of ethylene and a-olefins, respectively. In contrast, Pd-and Ni-diimine catalysts afford polyethylenes with highly branched structures and poly(a-olefin)s containing non-branched polymethylene repeating units, respectively (Scheme 2 (I)).…”
Section: Introductionmentioning
confidence: 99%
“…Herein we only discuss the nickel and palladium-based catalysts due to their single-site type nature with excellent controllability on the polymer MWs and PDIs. [73][74][75] Table 4 summarizes the detailed polymerization results of these late transition metal catalysts. Zhu and co-workers [ 76 ] found that long-chain branched PEs with a broad or bimodal MWD could be prepared with a novel nickel(II)-diimine catalyst system using 2,3-bis(2-phenylphenyl)butane diimine nickel dibromide/ MMAO.…”
Section: Late Transition Metal Catalystsmentioning
confidence: 99%